FOSTERING BALANCED THINKING THROUGH HOLISTIC MODERATION EDUCATION: A STUDY OF THE URBAN MUSLIM SOCIETY - Primarni, Amie; Yusof, Nabilah; Nuhdi, Asep; Makmudi, Makmudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
This study examines the application of moderation education based on a holistic approach as the key to building a balance of thinking to overcome radicalism and intolerance, especially in the context of the Contemporary Urban Muslim Society. This holistic approach integrates intellectual, emotional, social, and spiritual aspects to form a moderate, tolerant, and open-minded character, relevant to urban challenges such as cultural pluralism, secularism, and global information penetration. The study uses a qualitative method with a phenomenological approach to explore the lived experiences and perspectives of students, educators, principals, and parents in educational institutions implementing holistic moderation education. Data were collected through in-depth interviews, participant observation, and document analysis to understand how moderation values are internalized in everyday learning practices. The findings show that the balance of thought resulting from holistic education effectively enhances critical thinking, empathy, and appreciation for diversity, key foundations in preventing extremism. In urban Muslim communities, interactive learning methods such as group discussions, cross-cultural studies, and project-based learning are essential to support the internalization of moderate values in complex social environments. The novelty of this study lies in its phenomenological insight into how holistic education fosters inclusive, progressive, and peace-oriented Muslim youth. However, the scope of this study is limited to urban Muslim settings, and the findings may not fully represent broader or rural contexts. This approach is expected to offer a contextual model for cultivating tolerance and resilience in global social dynamics while staying rooted in Islamic values.